EFFECT OF IMMERSION TYPE III GYPSUM IN SODIUM HYPOCHLORITE AND POVIDONE-IODINE SOLUTIONS ON THE NUMBER OF CANDIDA ALBICANS COLONIES - Moh. Basroni Rizal; Dwi Andriani; Yoga Pratama Putra (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2023)
Introduction: Cross-infection is the transfer of microorganisms that can occur from individual to individual or to object. Candida albicans is one of the infectious pathogens that can cause cross-infection in dentistry. One example is the manufacture of working models of gypsum material, which can cause cross-infection from patients to dentists or technicians, so it is necessary to control infection by means of    disinfection    of    type    III    gypsum     material     work models. Objective: To determine the effectiveness of soaking type III Gypsum in a 0.5% Sodium hypochlorite and 2% Povidone Iodine solution against the growth of Candida albicans. Methods: A laboratory experiment with a total of 21 samples, consisting of 7 samples for each group. The sample is made of a type III gypsum plate measuring 2 x 1 x 0.5 cm. The sample consisted of 3 groups: treatment 1, treatment 2, and treatment 3. The study used the diffusion method. Gypsum plate type III was contaminated with Candida albicans and then immersed in a solution of sterile distilled water (C), 0.5% sodium hypochlorite (P1), and 2% povidone-iodine (P2). The soaking results were planted in SDA media, incubated for 2x24 hours, and then counted using a colony counter. The data were analyzed using Kruskal- Wallis and Mann-Whitney post hoc analyses. Results: In the Kruskal- Wallis analysis of significance (p), between each group, there was a significant difference (p<0.05). The Mann-Whitney post hoc analysis test showed a correlation between group K and P1 and P2 (p<0.05). Conclusion: 0.5% Sodium Hypochlorite and 2% Povidone Iodine solutions are effective as disinfectants using the immersion method in Type III Gypsum against the growth of Candida albicans.